The International Disputes Within the Framework of the New World Order - السويدي, شکري (Dirasat in Economics and Business, 2011)
This study is concerned with the increasing phenomenon of international disputes in many regions in the world today. As we see, there are many internal and international conflics have emerged in many areas in the world and this puts a remarkable influence upon the establishment of this study can be indicated by saying despite that the world community has achieved tremendous progress in terms of technology, transportation and communication, th regiona and international disput.